Combining in-cell NMR and X-ray fluorescence microscopy to reveal the intracellular maturation states of human superoxide dismutase 1. Issue 3 (21st November 2014) - Luchinat, E.; Gianoncelli, A.; Mello, T.; Galli, A.; Banci, L.
Abstract : Combined in-cell NMR spectroscopy, X-ray fluorescence and optical fluorescence microscopies allow describing the intracellular maturation states of human SOD1. Abstract : An integrated approach which combines in-cell NMR spectroscopy with optical and X-ray fluorescence microscopy was developed to describe the intracellular maturation state of human Cu, Zn-SOD1. Microscopy data show a correlation between the intracellular levels of SOD1 and the content of zinc, corresponding to zinc binding to SOD1 observed by in-cell NMR.